2009
DOI: 10.1210/jc.2008-1689
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Weight Loss on Liver Free Fatty Acid Uptake and Hepatic Insulin Resistance

Abstract: The liver responds to a 6-wk period of calorie restriction with a parallel reduction in lipid uptake and storage, accompanied by enhancement of hepatic insulin sensitivity and clearance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
73
4
4

Year Published

2009
2009
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 107 publications
(91 citation statements)
references
References 31 publications
10
73
4
4
Order By: Relevance
“…The achieved weight loss led to a reduction in ALT and triglyceride levels at the end of the study comparable to related studies showing a parallel reduction in triglyceride uptake and liver-storage after a 6 week period of calorie restriction [35]. These results suggest a reduction in liver fat content in our patients as well.…”
Section: Discussionsupporting
confidence: 88%
“…The achieved weight loss led to a reduction in ALT and triglyceride levels at the end of the study comparable to related studies showing a parallel reduction in triglyceride uptake and liver-storage after a 6 week period of calorie restriction [35]. These results suggest a reduction in liver fat content in our patients as well.…”
Section: Discussionsupporting
confidence: 88%
“…Diet only interventions We identified 11 eligible study groups including 322 participants (approximately 65% women, 20 controls) prescribing dietary change: six using low-to-moderate fat/moderate-to-high carbohydrate energy restricted diets [25][26][27][28][29][30], one of which also specifically restricted iron intake [27]; three groups were given low carbohydrate ketogenic diets [26,31,32]; and two high protein diets [30,33]. Two studies employed biopsy [27,31], but only one at follow-up [31], the other used ALT and AST at follow-up [27]; three used 1 H-MRS [26,28,30], two used CT [25,32], three studies relied on ALT and AST [29,33].…”
Section: Study Findingsmentioning
confidence: 99%
“…Two studies employed biopsy [27,31], but only one at follow-up [31], the other used ALT and AST at follow-up [27]; three used 1 H-MRS [26,28,30], two used CT [25,32], three studies relied on ALT and AST [29,33]. Only two studies had a control group [25,27]; in one the control group were those with low adherence to the protocol [25].…”
Section: Study Findingsmentioning
confidence: 99%
“…44 Whether the hepatic benefit of exercise reflects lower adipose lipolysis and FFA availability and/or a direct effect on hepatic FFA uptake independent of FFA concentration is unclear. In the context of diet-induced weight loss, reductions in liver fat parallel the attenuation of hepatic FFA uptake despite similar basal FFA concentrations, 47 which suggests that the liver may not be a passive bystander with adipose tissue acting as the locus of control. Therefore, it has been suggested that hepatic fatty acid uptake may be regulated, 48 perhaps through altered expression and activity of fatty acid translocase or cluster of differentiation 36 (CD36).…”
Section: Nafld Pathophysiology and The Mechanism Of An Exercise Effectmentioning
confidence: 99%